Evaluation of Lateral and Vertical Dimensions of Micromolds Fabricated by a PolyJet™ Printer - Sindhu Vijayan (Micromachines, 2021)
PolyJet™ 3D printers have been widely used for the fabrication of microfluidic molds to replicate castable resins due to the ease to create microstructures with smooth surfaces. However, the microstructures fabricated by PolyJet printers do not accurately match with those defined by the computer-aided design (CAD) drawing. While the reflow and spreading of the resin before photopolymerization are known to increase the lateral dimension (width) of the printed structures, the influence of resin spreading on the vertical dimension (height) has not been fully investigated. In this work, we characterized the deviations in both lateral and vertical dimensions of the microstructures printed by PolyJet printers. The width of the printed structures was always larger than the designed width due to the spreading of resin. Importantly, the microstructures designed with narrow widths failed to reproduce the intended heights of the structures. Our study revealed that there existed a threshold width (wd′) required to achieve the designed height, and the layer thickness (a parameter set by the printer) influenced the threshold width. The thresholds width to achieve the designed height was found to be 300, 300, and 500 μm for the print layer thicknesses of 16, 28, and 36 μm, respectively. We further developed two general mathematical models for the regions above and below this threshold width. Our models represented the experimental data with an accuracy of more than 96% for the two different regions. We validated our models against the experimental data and the maximum deviation was found to be <4.5%. Our experimental findings and model framework should be useful for the design and fabrication of microstructures using PolyJet printers, which can be replicated to form microfluidic devices.